ELECTRONIC INFORMED CONSENT MODEL DEVELOPMENT FOR IMPLEMENTATION IN CLINICAL TRIALS IN UKRAINE - Vy, Dobrova; KО ZUPANETS; Ty, Kolodyezna; yv, Timchenko (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The process of signing the informed consent (IC) is one of the essential procedures during organizing and conducting the clinical trial (CT) of any new drug. During this procedure, the volunteers should read the IC form that is often difficult to understand. Analysis of literature showed lack of experience in use of electronic systems in the IC signing in Ukraine. Abroad such systems are quite new. Thus, the aim of this work is the rationale for the introduction of electronic IC to CT drugs in Ukraine and the development of its general model. Methods: Experience in the use of electronic systems in IC signing analysis was carried out using methods of system analysis, synthesis, abstraction, and generalization. Results: Thus, during the signing process of paper forms risks and errors may arise such as loss of paper copies and signing of an incorrect version of the document by the volunteer. With the use of electronic forms, it is possible to prevent three categories of risks in preparation and signing, such as risks in the development, use, and auditing of IC forms. The opportunities of the electronic IC system to protect trial subjects in its use during organizing and conducting of CT were showed. Conclusions: The study showed that such systems are effective. Therefore, it seems appropriate to introduce electronic IC in CT of new drugs in Ukraine. We have formulated requirements to the system and determined its structure for optimal use.